If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 36 = w + 5w Combine like terms: w + 5w = 6w 36 = 6w Solving 36 = 6w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6w' to each side of the equation. 36 + -6w = 6w + -6w Combine like terms: 6w + -6w = 0 36 + -6w = 0 Add '-36' to each side of the equation. 36 + -36 + -6w = 0 + -36 Combine like terms: 36 + -36 = 0 0 + -6w = 0 + -36 -6w = 0 + -36 Combine like terms: 0 + -36 = -36 -6w = -36 Divide each side by '-6'. w = 6 Simplifying w = 6
| 5(8+7x)=390 | | -6x+4(x+8)=30 | | 5a-3whena=4 | | 12u-5u=56 | | F(8)=10-2x | | a^2+12a-47=0 | | 32=8v+5(v-4) | | 6(x+2)-2x=28 | | X-pie=pie | | 2(x+8)=-2x | | 2sin(-x)=0 | | 10(1+36)=20 | | x^4+x^2=684 | | -5.5+3.5(1-4s)=-20.5 | | tan63=34/x | | 15000=50*x^2/2 | | 3-(4x-2)=27 | | 3y^2-11y-16=0 | | 18=8v-4(v+8) | | (4x+3)(x)=320 | | 6n+3=3[-7n+1] | | (4x+5)(x)=400 | | 4+6[6-3n]=-5n-25 | | g^2+11g-152=0 | | -5u=-6u+6 | | (x+3)-3(x-2)=16 | | -f=f+10 | | 6x-7y+3x-2y= | | x^2-42y^2=1 | | 9+8b=9b | | -20+14x=10x+16 | | -7v+10=-9v |